Hybrid perovskite by mixing formamidinium and methylammonium lead iodides for high-performance planar solar cells with efficiency of 19.41%. (15th November 2017) - He, Xin; Guo, Panfeng; Wu, Jihuai; Tu, Yongguang; Lan, Zhang; Lin, Jianming; Huang, Miaoliang
Graphical abstract: FAPbI3 improves the quality of mixed perovskite layer and enhances the efficiency of planner solar cell from 15.95% to 19.41%. Highlights: Cation-mixed methylammonium and formamidinium perovskite (MA1−x FAx PbI3 ) is made. The cation-mixed perovskite has better crystallinity and larger grain than MAPbI3 . MA1−x FAx PbI3 has less defects and longer charge carrier lifetime than MAPbI3 . Planer perovskite solar cell with MA0.5 FA0.5 PbI3 gets a high efficiency of 19.41%. While the perovskite solar cell with pristine MAPbI3 gets an efficiency of 15.95%. Abstract: Organic lead halide layer is crucial to a high-efficiency planar perovskite solar cell. In order to reduce defects and improve the crystallinity of the perovskite layer, we introduce formamidinium lead iodide (FAPbI3 ) as crystal seeds to modulate the growth of methylammonium lead iodide (MAPbI3 ) crystals and form a mixed-cation perovskite layer (MA1−x FAx PbI3 ) by a facial two-step spin-coating method. The field-emission scanning electron microscopy and X-ray diffraction pattern show the better crystallinity and larger grain for mixed-cation perovskite layer than the pristine MAPbI3 layer. Time-resolved photoluminescence decay measurements indicate that the mixed perovskite layer has less defect and longer lifetime for charge recombination than pristine MAPbI3 layer. Under optimal conditions, the planar perovskite solar cell based on MA0.5 FA0.5 PbI3 achieves a champion power conversion efficiency (PCE) of 19.41%, while the planar perovskite solar cell based on pristine MAPbI3 obtains a PCE of 15.95% under the same conditions.